2014
DOI: 10.12740/pp/21865
|View full text |Cite
|
Sign up to set email alerts
|

Herbal remedies in depression – state of the art.

Abstract: Recent decades have seen development of research and an increased interest in the psychopharmacology of natural remedies. More than 20 herbal remedies have been identified that may potentially be applied in medicine as antidepressive, anxiety relieving or sleep-inducing agents. Patients often prefer to take herbal remedies and often take them on their own, without consulting a physician. The aim of the study is to present the state of the art concerning the use of natural remedies in the treatment of depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Moreover, the plant can interact with nonsteroidal anti-inflammatory drugs and thereby increase the risk of bleeding. Its interactions with statins and oral contraceptives have also been described (Nicoletti, 2012;Smeriglio et al, 2014;Szafrański, 2014). Interviewees sometimes reported suffering from dyslipidemia (14.47%, Table II), as well as using simvastatin to treat it (7.63%, Table VI).…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the plant can interact with nonsteroidal anti-inflammatory drugs and thereby increase the risk of bleeding. Its interactions with statins and oral contraceptives have also been described (Nicoletti, 2012;Smeriglio et al, 2014;Szafrański, 2014). Interviewees sometimes reported suffering from dyslipidemia (14.47%, Table II), as well as using simvastatin to treat it (7.63%, Table VI).…”
Section: Resultsmentioning
confidence: 95%
“…In several controlled clinical trials, saffron was shown to be more effective for mild to moderate depression than placebo and standard drugs. It is noteworthy that treatment with saffron is currently known to be the second leading herbal treatment for depressive symptoms [25,28,70] and in comparison with hypericum extracts, it does not cause immune system problems. Experiments on other herbal remedies such as lavender, borage, chamomile and ginseng have demonstrated antidepressant effects, but it should be emphasized that they have not yet been definitely proven [28].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the desirable health effects of herbal drugs are largely due to their antioxidant properties and potential impact on cellular metabolism [28]. Medicinal plants can regulate neurotransmission by directly affecting receptors or the synthesis and distribution of neurotransmitters, or by regulating immunological processes [29].…”
Section: Effective Medicinal Plants On Depressionmentioning
confidence: 99%
“…Discontinuation should be seen here as distinct from the withdrawal scenario associated with alcohol and other addictive substances, a scenario which commonly presents together with craving, drug seeking behavior, and the inability to stop drug use [71,72]. Thus, if a discontinuation of clozapine is needed, the molecule should be gradually tapered off over several weeks rather than abruptly discontinued, except in cases of emergency (e.g., agranulocytosis), and only with close clinical monitoring [10,67,73]. There are no established guidelines regarding which antipsychotic to choose after withdrawal of clozapine [73], although anticholinergics and olanzapine may be the treatment of choice for preventing withdrawal [53].…”
Section: Discussionmentioning
confidence: 99%